Response of tree species diversity to disturbance in humid tropical forests of Borneo. (17th March 2016) - Imai, Nobuo; Samejima, Hiromitsu; Demies, Malcom; Tanaka, Atsushi; Sugau, John Baptist; Pereira, Joan T.; Kitayama, Kanehiro
Abstract: Questions: The intermediate disturbance hypothesis (IDH) predicts that the highest species diversity occurs at an intermediate level of disturbance. The validity of the IDH remains contentious in tropical forests because the IDH has been supported in tropical dry forests but often not in humid tropical forests. We addressed the following questions: (1) is the IDH valid in humid tropical forests of Borneo; (2) how does the disturbance index (DI) influence conformity to the IDH; and (3) does the rainfall regime influence conformity to the IDH within the tropical biome? Location: Humid tropical forests of northern Borneo. Methods: We established approximately 50 20‐m radius circular plots across primary to highly degraded forests in each of three logging concessions. Species richness was regressed against the following four DIs: above‐ground biomass (AGB), relative number (RNO) of pioneer trees, average wood density, and the principal component analysis (PCA) axis 1 score for the three DIs. For studies that examined the IDH in tropical forests, the relationship between total and dry season precipitation and the percentage reduction in species diversity from a unimodal maximum to the lowest disturbance level was examined. Results: Species richness peaked at intermediate disturbance levels when average wood density and PCA 1 score, but not AGB and pioneer RNO, were used as DIs. The peaks were relatively flat, with 8–11% reduction in species richness from a unimodal maximum to the lowest disturbance level. The percentage reduction in species richness from a unimodal maximum to the lowest disturbance level increased with decreasing total and dry season precipitation within the tropical biome. Conclusion: Species richness showed a unimodal response to disturbance, but conformity to the IDH varied with DI because different DIs may have different biological meanings. Species richness changed little from a moderately disturbed to the least disturbed stand in humid tropical forests compared with tropical dry forests, indicating that IDH is dependent on rainfall regime. Abstract : We found the intermediate disturbance hypothesis (IDH) pattern in humid tropical forests of Borneo. But, conformity to the IDH varied with disturbance index used (aboveground biomass, pioneer's abundance, and average wood density). Our meta‐analysis found that the IDH pattern varies depending on rainfall regime within tropical biomes;a clearer unimodal pattern occurs with decreasing rainfall.